Depletion of RNASEH2 Activity Leads to Accumulation of DNA Double-strand Breaks and Reduced Cellular Survivability in T Cell Leukemia. Issue 12 (30th June 2022) - Ghosh, Dipayan; Kumari, Susmita; Raghavan, Sathees C.
Graphical abstract: Highlights: Ribonuclease H2 (RNaseH2) function is crucial for maintaining genome integrity. RNASEH2A/RNASEH2B knockdown leads to loss of cell viability in T-ALL cell lines. RNASEH2A/RNASEH2B depletion leads to reduced DSB repair through NHEJ in MOLT4 cells. DSB repair is retarded in MOLT4 and Jurkat cells upon RNASEH2A/RNASEH2B depletion. RNase H2 is important for viability of T-ALL cells and is a plausible drug target. Abstract: Ribonuclease H2 (RNase H2) is a member of the ribonuclease H family of enzymes involved in removal of RNA from RNA-DNA hybrids as well as ribonucleotides which get misincorporated into the genomic DNA. Recent studies have shown that RNase H2 function is also needed for successful DNA repair through NHEJ events where DNA pol µ uses ribonucleotides during the gap filling stage. Mammalian RNase H2 is composed of three subunits, RNASEH2A, RNASEH2B and RNASEH2C. There have been studies suggesting changes in expression of these genes in various cancers of breast, prostate, colon, liver, and kidney. In this study, we have investigated the functional role of RNASEH2A and RNASEH2B in leukemic T-cells, MOLT4 and Jurkat. shRNA mediated knockdown of RNASEH2A/ RNASEH2B expression led to reduced cell survival and increase in apoptotic cell population. Importantly, knockdown of RNASEH2A or RNASEH2B, led to cell cycle arrest at S phase and increased number of 53BP1 foci due to abrogation of NHEJ. Interestingly, RNASEH2A or RNASEH2B depleted cells showed significantly retarded DSB repair kinetics compared to scrambled shRNA control, when exposed to ionizing radiation suggesting that NHEJ is abrogated due to loss of RNASEH2 activity in T-ALL cells. Thus, we uncover the importance of RNase H2 function in leukemic cells and suggest that it can be targeted for cancer therapy.